Say you still love me : a novel - Tucker, K. A. (Kathleen A.), 1978- (Atria Paperback, 2019)
Life is a mixed bag for Piper Calloway. On the one hand, she<U+2019>s a twenty-nine-year-old VP at her dad<U+2019>s multibillion-dollar real estate development firm, and living the high single life with her two best friends in a swanky downtown penthouse. On the other hand, she<U+2019>s considered a pair of sexy legs in a male-dominated world and constantly has to prove her worth. Plus she<U+2019>s stuck seeing her narcissistic ex-fiancé<U+2014>a fellow VP<U+2014>on the other side of her glass office wall every day. Things get exponentially more complicated for Piper when she runs into Kyle Miller<U+2014>the handsome new security guard at Calloway Group, and coincidentally the first love of her life. The guy she hasn<U+2019>t seen or heard from since they were summer camp counselors together. The guy from the wrong side of the tracks. The guy who apparently doesn<U+2019>t even remember her name. Piper may be a high-powered businesswoman now, but she soon realizes that her schoolgirl crush is still alive and strong, and crippling her concentration. What<U+2019>s more, despite Kyle<U+2019>s distant attitude, she<U+2019>s convinced their reunion isn<U+2019>t at all coincidental, and that his feelings for her still run deep. And she<U+2019>s determined to make him admit to them, no matter the consequences.